Examining processes in research and development at the department of science and technology - Jose Ramon G. Albert; Donald B. Yasay; Raymond E. Gaspar (Philippine Institute for Development Studies (PIDS), 2016)
Research and development (R and D) activities have long been recognized as one of the critical components to improve a country's productivity and competitiveness as well as people's well-being. Notable advancements in agriculture (to develop new variety of crops), health (to improve nutrition and combat various diseases), industry (to develop new products and services), as well as in climate change adaptation and mitigation are products of R and D. The Department of Science and Technology (DOST), chiefly through sectoral councils and R and D performers, has been successfully undertaking or supporting a considerable share of R and D activities in the country while noting limited resources available. However, there is a need to improve the thrust for R and D, which may require the conduct of an R and D summit to finalize the scope of the government's R and D medium- and long-term agenda. The DOST also needs to reexamine the distribution of grant-in-aid funds to R and D institutes and identify breakdowns of R and D funding for basic research, applied research, and development. The DOST may need to pilot test scientific methods, such as Analytic Hierarchy Processes, for selection of R and D proposals for funding by its sectoral councils.
Keywords: 330